Gestational diabetes mellitus and its fetomateranal outcome: a prospective observational study - Zalavadia, Vidhi; Rathod, Tarun K.; Patel, Mitulkumar P.; Shilu, Hemangi J.; Nagar, Rinal N.; Sahani, Nidhi D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Gestational diabetes mellitus (GDM) is a common metabolic disorder of pregnancy associated with significant maternal, fetal, and long-term metabolic complications. It contributes to hypertensive disorders, operative delivery, neonatal morbidity, and increased future risk of type 2 diabetes in both mother and offspring. Evaluating fetomaternal outcomes in GDM is essential for improving clinical management and reducing adverse pregnancy outcomes. Methods: A prospective observational study was conducted among 100 antenatal women, including 60 diagnosed with GDM and 40 with normal glucose tolerance for 18 months from September 2023 to February 2025. Participants were followed throughout pregnancy to assess maternal complications, delivery outcomes, neonatal health, and the influence of glycemic control. Clinical, laboratory, and outcome data were systematically recorded and analyzed using appropriate statistical methods, with significance set at p≤0.05. Results: GDM pregnancies demonstrated higher maternal morbidity, including increased pre-eclampsia (28% versus 10%), caesarean delivery (55% versus 30%), and postpartum complications compared with non-GDM pregnancies. Neonatal complications were also more frequent in the GDM group, particularly macrosomia (25% versus 5%), hypoglycemia (18% versus 5%), respiratory distress, and greater neonatal intensive care unit admissions with longer hospital stay. Poor glycemic control and insulin-treated cases were associated with worse maternal and fetal outcomes. Postpartum follow-up indicated progression to type 2 diabetes in a proportion of mothers, highlighting persistent metabolic risk. Conclusions: GDM is strongly associated with adverse maternal and neonatal outcomes as well as long-term metabolic consequences. Early detection, strict glycemic control, individualized management, and sustained postpartum surveillance are essential to reduce complications and improve both immediate and future health outcomes.